Vinylester / glass fiber interface: Still a key component for designing new styrene-free SMC composite materials. (12th April 2020) - Bénéthuilière, T.; Duchet-Rumeau, J.; Dubost, E.; Peyre, C.; Gérard, J.F.
Abstract: Sheet molding compounds (SMC) allow to design high performance polymer-matrix composites increasingly used for structural applications in the automotive industry. SMC are usually based on an unsaturated polyester thermosetting resin diluted in styrene with chopped glass fibers and fillers. Due to international regulations linked with the potential risks of styrene, replacing such styrene-based reactive system compound is becoming more and more strategic in order to zero-VOC emission, while keeping similar (or displaying even better) mechanical properties and shrinkage control to conventional SMC-based composite materials. In this study, the same sized E-glass fiber was combined with two different vinylester matrices, a conventional styrene containing resin and a styrene free one. The second type fits more suitable for friendly environmentally purposes as it is based on a dimethacrylate diluent. The objective of this work is focused on interfacial adhesion in both systems as the fiber/matrix interface is a key parameter governing the mechanical properties of the final composite materials. A multiscale analysis was carried out from: i) the fiber scale by measuring the interfacial shear stress by using the microdebonding test; ii) the fibers bundle scale by studying the wettability of fibers by the uncured resin; iii) up to the mechanical characterization of unidirectional SMC composites by measuring the interlaminar shear strength (ILSS). As main results, it is demonstrated that the styrene-free composites have a suitable interfacial resistance compared to conventional systems whereas impregnation, i.e. specific fiber sizings which will be more soluble in the resin-dimethacrylate reactive system need to be designed.